Analisis Wacana Kritis terhadap Kampanye Boikot Starbucks di X : Analisis Wacana Kritis terhadap Kampanye Boikot Starbucks di X - Raden Sasnitya; Wawan Gunawan; Mahardika Zifana; Adam Muhammad Nur (RETORIKA: Jurnal Ilmu Bahasa, 2025)
The pro-Israel product boycott campaign, initiated in October 2023, has had a significant impact on consumer behavior, particularly within the coffee industry. Starbucks, often perceived as linked to Israel, has been one of the brands most affected by this movement. This study employs a Critical Discourse Analysis (CDA) approach to examine the linguistic features and underlying motivations expressed in the discourse surrounding the boycott, with a specific focus on Starbucks in discussions on X (formerly Twitter) in Indonesia. CDA is particularly suited for this study as it allows for an in-depth exploration of power dynamics, ideological positioning, and social influences embedded in digital discourse. Using Martin and White’s Appraisal Theory, the research analyzes how attitudes—expressed through affect, judgment, and appreciation—shape language choices and construct interpersonal meanings in boycott-related discussions, revealing how public sentiment is mobilized and reinforced through discourse. The analysis identifies three dominant types of attitudes: judgment, appreciation, and affect, with judgment being the most prevalent. The findings suggest that the discourse reflects strong sentiments of anger and concern toward the Israel-Palestine conflict, as well as a collective stance in support of the boycott. These attitudes are expressed through language that critiques Starbucks and expresses solidarity with the Palestinian cause. The study’s time frame, spanning from October 25, 2023, to August 15, 2024, may limit the scope of the findings, but provides a focused view of the discourse during a key period in the boycott movement. This research contributes to understanding how social media discourse shapes consumer activism and the public’s relationship with global brands during politically charged times.